Comparing low volume of blood flow restricted to high-intensity resistance training of the finger flexors to maintain climbing-specific strength and endurance: a crossover study - Javorský, T.; Saeterbakken, A. H.; Andersen, V.; Baláš, J. (Frontiers in Sports and Active Living, 2023)
Introduction: It is acknowledged that training during recovery periods after injury involves reducing both volume and intensity, often resulting in losses of sport-specific fitness. Therefore, this study aimed to compare the effects of high-intensity training (HIT) and low-intensity training with blood flow restriction (LIT + BFR) of the finger flexors in order to preserve climbing-specific strength and endurance.